Anaplasma phagocytophilum Encephalitis: A Case Report and Literature Review of Neurologic Manifestations of Anaplasmosis - Ronin Joshua S. Cosiquien; Nenad Stojiljkovic; Charles W. Nordstrom; Emeka Amadi; Larry Lutwick; Igor Dumic (MDPI AG, 2023)
Anaplasma phagocytophilum is an obligate intracellular, Gram-negative pathogen, causative agent of Human Granulocytic Anaplasmosis (HGA). HGA usually manifests as a non-specific febrile illness, accompanied by evidence of leucopenia, thrombocytopenia, and an alteration in liver enzymes. Neurologic manifestations of anaplasmosis are rare and rarely reported. We describe a 62-year-old man who developed encephalitis due to an Anaplasma phagocytophilum infection. The patient favorably responded to intravenous doxycycline and recovered without neurological sequela. In the tick endemic area, clinicians should have a high index of suspicion for tick-borne diseases in patients presenting with neurological deficits. A prompt diagnosis and treatment lead to improvements in morbidity and mortality.